Uptake of (3)H-Tetracycline by Resistant and Sensitive Escherichia coli - Reynard, A. M. (1971)
The uptakes of (3)H-tetracycline by 12 tetracycline-sensitive and 24 tetracycline-resistant Escherichia coli hospital cultures were found to be 270 and 75 nmoles of tetracycline per milliliter of cell water per 20 min, respectively. This confirms reports by other investigators who, by using only one or two cultures, suggested a relationship between tetracycline uptake and tetracycline resistance. However, minimum inhibitory concentrations of tetracycline for the cultures bore no relation to the tetracycline uptake values, suggesting that loss of tetracycline uptake may not be the primary cause of resistance. In addition there were three resistant cultures with uptake values greater than 140 and two sensitive cultures with uptakes lower than 180, raising the question of how these tetracycline-resistant cultures could grow with tetracycline at concentrations nearly as high as those found to inhibit growth of sensitive organisms. Of the tetracycline-resistant cultures, 15 were able to transfer tetracycline resistance to a recipient organism and 9 were not. Two of the cultures transferred TC-resistance to a recipient with no modification-restriction system (E. coli C) but did not transfer resistance to a recipient with a known modification-restriction system (E. coli K-12).